Strategi Manajemen untuk Kontrol Tekanan Darah pada Pasien Pra-Operasi Elektif: Berfokus pada Peningkatan Dukungan Keluarga, Kontrol Kecemasan, dan Perilaku Peduli di Ruang Penerima - Haryanti, Titik (Universitas Faletehan, 2023)
Surgery can be generally defined as a medical action that causes a stressor on a person's integrity, resulting in a stress response, both psychological and physiological. It is totally normal to feel anxious before surgery. This study aimed to identify the management strategies for blood pressure control in elective pre-surgery patients, focusing on family support improvement, anxiety control, and caring behavior. It was an analytical-correlational study which the total samples were 130 respondents at the receiving room of Malang Lavalette Hospital. The data analysis confirmed significant relationships in elective pre-surgery patient care. Family support and nurses' caring behavior had notable impacts on patient anxiety with p values of 0.000 and 0.034 respectively. Moreover, family support and anxiety, as well as anxiety and blood pressure, demonstrated significant associations with p values of 0.000. Notably, family support exhibited a direct effect on blood pressure (0.568) greater than its indirect effect through anxiety (0.453), summing to a total effect of 1.021. Similarly, nurses' caring behavior had a direct effect on blood pressure (0.1225) exceeding its indirect effect through anxiety (0.1099), resulting in a total effect of 0.2324. The researchers found that there was an effect of elective pre-surgery patients management strategies on blood pressure control in terms of increasing family support, anxiety control and caring behavior in receiving room.